2022
DOI: 10.3390/plants11060724
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Map of the Research on Disease Modelling for Agricultural Crops Worldwide

Abstract: In this work, we developed a systematic map to identify and catalogue the literature pertaining to disease modelling for agricultural crops worldwide. Searches were performed in 2021 in the Web of Science and Scopus for papers reporting any type of disease model for 103 crops. In total, 768 papers were retrieved, and their descriptive metadata were extracted. The number of papers found increased from the mid-1900s to 2020, and most of the studies were from North America and Europe. More disease models were ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 44 publications
1
1
0
Order By: Relevance
“…Wheat (37 simulations) was most often investigated, followed by rice (15 simulations), grapevine (13 simulations) and potato (11 simulations) (Table 2). This is in agreement with Fedele et al (2022) who reported that most articles related to crop disease modelling in general are related to wheat, potato, grapevine and apple, whereby apple is obviously under-represented in climate change impact research (Table 1). Many other important crops such as barley and soybean are also under-represented in crop disease risk simulations, or completely "set aside" such as oat and rye (Table 1).…”
Section: Crop Plant Species Simulatedsupporting
confidence: 91%
“…Wheat (37 simulations) was most often investigated, followed by rice (15 simulations), grapevine (13 simulations) and potato (11 simulations) (Table 2). This is in agreement with Fedele et al (2022) who reported that most articles related to crop disease modelling in general are related to wheat, potato, grapevine and apple, whereby apple is obviously under-represented in climate change impact research (Table 1). Many other important crops such as barley and soybean are also under-represented in crop disease risk simulations, or completely "set aside" such as oat and rye (Table 1).…”
Section: Crop Plant Species Simulatedsupporting
confidence: 91%
“…Mathematical models can help growers schedule fungicide sprays ( Pertot et al., 2017 ; Rossi et al., 2019 ; Fedele et al., 2022 ). Models have been developed to understand the epidemiology of anthracnose on specific crops and to support infection-risk-based fungicide applications ( Dodd et al., 1991 ; Park et al., 1992 ; Monroe et al., 1997 ; Moral et al., 2012 ; Singh, 2020 ).…”
Section: Introductionmentioning
confidence: 99%